Kajian tentang keberhasilan kebijakan kemitraan usaha besar menengah kecil (Pengembangan metodologi evaluasi kebijakan dan penerapannya pada program tebu rakyat Indonesia) - Wijanto Hadipuro (Economic Journal of Emerging Markets, 2000)
There are nine forms of regulation used by Indonesian government to induce the cooperation between large and medium with small enterprises. Content analysis on the regulations shows that each regulation has its own objectves without any goals to specify the objectives, that makes it difficult to evaluate the success of each program.